The Level of Bullying among Females Attending Physical Fitness Centers in the Governorate of Al-Karak - Al-Sarayreh, Aya Fahid; Al-dmour , Belal Awad (Dirasat: Educational Sciences, 2023)
Objective: This study aimed to identify the levels of bullying among females at fitness centers in Al-Karak governorate. Method: The study utilized the descriptive social survey method with the use of a questionnaire. To achieve the study's objective, a questionnaire was developed to collect data, and its validity and reliability were verified. The questionnaire was distributed among a sample of (65) female participants from (10) physical fitness centers in the governorate. Results: The results showed that the overall average for the level of bullying/victims among females in fitness centers was low. Emotional bullying/victims ranked the highest, followed by verbal bullying/victims, and then by physical bullying/victims. Social bullying/victims ranked fourth. The results also revealed significant differences between the means of the level of bullying/victims among female members of fitness centers according to variables such as age, place of residence, marital status, having children, and level of education. However, these differences were not statistically significant at the level of (α≤0.05) concerning the level of bullying/victims among female members of fitness centers. The study further indicated that physical bullying is the most common type of bullying that leads to discontinuity in female sports institutions' operations. Conclusions: The study recommends the maintenance of a bully-free environment in fitness centers, along with increased awareness about the nature of bullying and its consequences for both the bully and the bullied (victim). Furthermore, it advocates for a zero-tolerance policy towards any type of bullying, whether verbal, physical, social, or emotional.